Adsorption of Acid Red 18 from Aqueous Solution onto Activated Carbon Prepared from Murraya koenigii (Curry Tree) Seeds - Suresh, S.; Wilfred Sugumar, R.; Maiyalagan, T. (Asian Journal of Chemistry, 2010)
This paper focuses on the adsorption of acid red 18 onto low cost adsorbent prepared from Murraya koenigii seeds (MKS) from aqueous solutions at room temperature (25 ºC). Batch experiments were conducted and the effect of different process parameters such as adsorbent dosage and initial dye concentration were studied. The adsorption isotherm data was analyzed using Langmuir, Freundlich and Temkin isotherm models. The equilibrium data fits well with Langmuir adsorption isotherm and the monolayer adsorption capacity was found to be 53.19 mg/g. The adsorption kinetics was studied using pseudo-first order and pseudo-second order models. The rate of adsorption was found to conform to pseudo-second order kinetics with a good correlation (R2 > 0.99). The activated carbon prepared was characterized by SEM and FTIR spectra. The results prove that Murraya koenigii seeds is a good low cost adsorbent for the removal of acid red 18 from aqueous solution.